The Finale of the Wisdom of Solomon: Its Context, Translation and Significance * - Jones, Ivor H. (Journal for the study of the pseudepigrapha, 2009)
In this article a detailed examination of the language, context, content and function of Wis. 19.18-22 is offered, one which throws light on the literary structure and character of the whole book and its religious and cultural setting. Particular attention is given to the translation of Wis. 19.18 and to its musical terms and imagery. This approach leads to fresh conclusions regarding the references in the book to the cosmic elements, conclusions which are significant both for the book as a whole and for tracing the extensive literary history of that phrase. Finally, the light thrown here on the structure and character of the book is used to provide criteria for the assessment of recent hypotheses regarding its main features.